ASSESSMENT DEVELOPMENT BASED SCIENCE PROCESS SKILLS ON MATERIAL FACTORS AFFECTING CHEMICAL EQUILIBRIUM - Igusti made astawa; Noor Fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research aims to produce science process skills based assessment (PPP) on the material factors that affect the chemical equilibrium in the form of questions and multiple-choice test essay. The research method used is the Research and Development (Research and Development). Research subjects is. assessment development based science process skills on material factors affecting chemical equilibrium. Limited testing result that assessment based on material science process skills the factors that affect these chemical equilibria are based on aspects of suitability, skill-based assessment is the process of science is in accordance with the SK-KD and can measure indicators of students' science process skills. Science process skills based assessment has a high level of kemenarikan. Science process skills based assessment has a very high level of legibility. This assessment is also presented through multiple representations of macroscopic, submikroskopis, and symbolic.Keywords: assessment, test questions, chemical equilibrium, science process skills